Metal-free formal synthesis of phenoxazine - Kervefors, Gabriella; Becker, Antonia; Dey, Chandan; Olofsson, Berit (Beilstein Journal of Organic Chemistry, 2018)
A transition metal-free formal synthesis of phenoxazine is presented. The key step of the sequence is a high-yielding O-arylation of a phenol with an unsymmetrical diaryliodonium salt to provide an ortho-disubstituted diaryl ether. This species was cyclized to acetylphenoxazine in moderate yield. The overall yield in the three-step sequence is 72% based on recovered diaryl ether. An interesting, unusually stable iodine(III) intermediate in the O-arylation was observed by NMR and could be converted to the product upon longer reaction time.
Keywords: arylation; cyclization; diaryl ether; diaryliodonium salt; phenol

(untitled) - Katsamakas, S.; Zografos, A. L.; Sarli, V. (Curr. Med. Chem., 2016)

(untitled) - Hernandez-Olmos, V.; Abdelrahman, A.; El-Tayeb, A.; Freudendahl, D.; Weinhausen, S.; Müller, C. E. (J. Med. Chem., 2012)

(untitled) - Thimmaiah, K. N.; Easton, J. B.; Germain, G. S.; Morton, C. L.; Kamath, S.; Buolamwini, J. K.; Houghton, P. J. (J. Biol. Chem., 2005)

(untitled) - Moosmann, B.; Skutella, T.; Beyer, K.; Behl, C. (Biol. Chem., 2001)

(untitled) - Zhao, Y.-q.; Yin, Y.-q.; Liu, J.; Wang, G.-h.; Huang, J.; Zhu, L.-j.; Wang, J.-h. (Acta Pharmacol. Sin., 2016)

(untitled) - Prinz, H.; Chamasmani, B.; Vogel, K.; Böhm, K. J.; Aicher, B.; Gerlach, M.; Günther, E. G.; Amon, P.; Ivanov, I.; Müller, K. (J. Med. Chem., 2011)

Medicinal Chemistry of Anticancer Drugs - Avendaño, C.; Menéndez, J. C. (Elsevier, 2008)

(untitled) - Gao, S.; Takano, T.; Sada, K.; He, J.; Noda, C.; Hori-Tamura, N.; Tomoda, A.; Yamamura, H. (Br. J. Pharmacol., 2002)

(untitled) - Martinez, V.; Henary, M. (Chem. – Eur. J., 2016)

(untitled) - Yang, X.-B.; Yang, B.-X.; Ge, J.-F.; Xu, Y.-J.; Xu, Q.-F.; Liang, J.; Lu, J.-M. (Org. Lett., 2011)

(untitled) - Karlsson, K. M.; Jiang, X.; Eriksson, S. K.; Gabrielsson, E.; Rensmo, H.; Hagfeldt, A.; Sun, L. (Chem. – Eur. J., 2011)

(untitled) - Tian, H.; Yang, X.; Cong, J.; Chen, R.; Liu, J.; Hao, Y.; Hagfeldt, A.; Sun, L. (Chem. Commun., 2009)

(untitled) - Pearson, R. M.; Lim, C.-H.; McCarthy, B. G.; Musgrave, C. B.; Miyake, G. M. (J. Am. Chem. Soc., 2016)

(untitled) - Bernthsen, A. (Ber. Dtsch. Chem. Ges., 1887)

(untitled) - Eastmond, G. C.; Gilchrist, T. L.; Paprotny, J.; Steiner, A. (New J. Chem., 2001)

(untitled) - Schmidt, D. M.; Bonvicino, G. E. (J. Org. Chem., 1984)

(untitled) - Bonvicino, G. E.; Yogodzinski, L. H.; Hardy, R. A., Jr (J. Org. Chem., 1961)

(untitled) - Thomé, I.; Bolm, C. (Org. Lett., 2012)

(untitled) - Liu, N.; Wang, B.; Chen, W.; Liu, C.; Wang, X.; Hu, Y. (RSC Adv., 2014)

(untitled) - Eregowda, G. B.; Kalpana, H. N.; Hegde, R.; Thimmaiah, K. N. (Indian J. Chem., 2000)

(untitled) - Zhang, L.; Huang, X.; Zhen, S.; Zhao, J.; Li, H.; Yuan, B.; Yang, G. (Org. Biomol. Chem., 2017)

(untitled) - Louillat-Habermeyer, M.-L.; Jin, R.; Patureau, F. W. (Angew. Chem., Int. Ed., 2015)

(untitled) - Lindstedt, E.; Ghosh, R.; Olofsson, B. (Org. Lett., 2013)

(untitled) - Jalalian, N.; Petersen, T. B.; Olofsson, B. (Chem. – Eur. J., 2012)

(untitled) - Jalalian, N.; Ishikawa, E. E.; Silva, L. F., Jr; Olofsson, B. (Org. Lett., 2011)

(untitled) - Aradi, K.; Tóth, B. L.; Tolnai, G. L.; Novák, Z. (Synlett, 2016)

(untitled) - Olofsson, B. (Top. Curr. Chem., 2016)

(untitled) - Merritt, E. A.; Olofsson, B. (Angew. Chem., Int. Ed., 2009)

(untitled) - Stuart, D. R. (Chem. – Eur. J., 2017)

(untitled) - Malmgren, J.; Santoro, S.; Jalalian, N.; Himo, F.; Olofsson, B. (Chem. – Eur. J., 2013)

(untitled) - Tinnis, F.; Stridfeldt, E.; Lundberg, H.; Adolfsson, H.; Olofsson, B. (Org. Lett., 2015)

(untitled) - Wang, M.; Huang, Z. (Org. Biomol. Chem., 2016)

(untitled) - Bielawski, M.; Aili, D.; Olofsson, B. (J. Org. Chem., 2008)

(untitled) - Zhu, M.; Jalalian, N.; Olofsson, B. (Synlett, 2008)

(untitled) - Ochiai, M. (Top. Curr. Chem., 2003)

(untitled) - Pinto de Magalhães, H.; Lüthi, H. P.; Togni, A. (Org. Lett., 2012)

(untitled) - Stridfeldt, E.; Lindstedt, E.; Reitti, M.; Blid, J.; Norrby, P.-O.; Olofsson, B. (Chem. – Eur. J., 2017)

(untitled) - Ozanne-Beaudenon, A.; Quideau, S. (Angew. Chem., Int. Ed., 2005)

(untitled) - Lucchetti, N.; Scalone, M.; Fantasia, S.; Muñiz, K. (Angew. Chem., Int. Ed., 2016)

(untitled) - Dohi, T.; Kato, D.; Hyodo, R.; Yamashita, D.; Shiro, M.; Kita, Y. (Angew. Chem., Int. Ed., 2011)

(untitled) - Stang, P. J.; Zhdankin, V. V. (J. Am. Chem. Soc., 1993)

(untitled) - Kitamura, T.; Furuki, R.; Nagata, K.; Taniguchi, H.; Stang, P. J. (J. Org. Chem., 1992)